Specialization, Firm Dynamics and Economic Growth - Jaehan Cho; Zhizhuang Ge (East Asian Economic Review (EAER), 2019)
Productivity in agriculture or services has long been understood as playing an important role in the growth of manufacturing. In this paper we present a general equilibrium model in which manufacturing growth is stimulated by non-manufacturing sectors that provides goods used in both research and final consumption. The model permits the evaluation of two policy options for stimulating manufacturing growth: (1) a country imports more non-manufacturing goods from a foreign country with higher productivity and (2) a country increases productivity of domestic non-manufacturing. We find that both policies improve welfare of the economy, but depending on the policy the manufacturing sector responses differently. Specifically, employment and value-added in manufacturing increase with policy (1), but contract with policy (2). Therefore, specialization of the import nonmanufactured goods helps explain why some Asian economies experience rapid growth in the manufacturing sector without progress in other sectors.
Keywords: F11; F43; F63; 330; Firm Heterogeneity; Firm Innovation; Economic Growth; Specialization; Unbalanced Sector Growth